Human settlements and productive sectors locations in The argentine patagonian plateau - Luis Alberto Bertani; María de los Ángeles Tesoniero; Lorena Alicia Conejeros Bilbao (Boletín Geográfico)
The present paper presents the evaluation of the possibility of a deep transformation in the area of the Patagonian plateau in the eastern sector of the Río Negro province, Argentina. The idea is based on a project to emplace an artificial lake to generate electricity in an absolute depression called “Bajo del Gualicho” (-72,0 m asl), which would connect with the sea in the San Matías Gulf in the Atlantic Ocean, about 25 km away, to take advantage of the amplitude of tides existing in that place. The project is endorsed by several Argentine universities and science and technology organizations such as the National Ministry of Science, Technology and Productive Innovation and researchers from the National Universities of Comahue, La Plata and Patagonia Austral. In order to promote the lake generation, the conditions about the implementation of related projects should be analyzed: the urban use of the lake ́s perimeter and the development of new agricultural and productive areas under irrigation, covering an area about 19000 hectares. The great limitation in this case is the lack of fresh water in this place that could be overcome with the extension of the canal that provides water to the San Antonio Oeste town with a derivation to the projected area. The paper proposes a selection of an area for the settlements taking into account different factors, such as soil and topography, wind exposure, access to fresh water and existent infrastructure such as roads. The selected sector occupies 2500 hectares located in the northern sector of the lake between the 8,0 m and 38,0 m, below the level of the plateau that surrounds the Gualicho basin, which has an approximate elevation of 160 m asl. The proposed agricultural development under irrigation would be located immediately to the east of the proposed urban sector, occupying a strip of the lake ́s perimeter of about 19,000 hectares. In recent field studies, transects lines have been carried out to verify their capacity for different crops. They have a sandy texture and their effective depth varies between 0.73 m and 1.40 m. which makes them suitable for crops such as olive, vine, forestation, fodder, etc.